2022
DOI: 10.1038/s41598-022-20316-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) for advanced pancreatic and periampullary adenocarcinoma

Abstract: Long term prognosis and 5-year survival for pancreatic adenocarcinoma (PDAC) remains suboptimal. Endoscopic ultrasound (EUS) guided RFA (EUS-RFA) is an emerging technology and limited data exist regarding safety and long-term outcomes. The aim of this study is to report safety-profile, feasibility and outcomes of EUS-RFA for advanced PDAC. Prospective review of patients with diagnosis of locally-advanced or metastatic PDAC undergoing EUS-RFA between October 2016 to March 2018 with long-term follow up (> 30 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…A recent longitudinal cohort study by Thosani et al [ 32 ] in 10 patients with pancreatic adenocarcinoma, where one to four RFA sessions per patient were performed, revealed that CA 19-9 levels decreased after 12 treatment sessions. Tumor size reduction of more than 50% was recorded in 3 patients.…”
Section: Innovation On Eus-guided Rfa In Pancreatic Malignancymentioning
confidence: 99%
“…A recent longitudinal cohort study by Thosani et al [ 32 ] in 10 patients with pancreatic adenocarcinoma, where one to four RFA sessions per patient were performed, revealed that CA 19-9 levels decreased after 12 treatment sessions. Tumor size reduction of more than 50% was recorded in 3 patients.…”
Section: Innovation On Eus-guided Rfa In Pancreatic Malignancymentioning
confidence: 99%
“…The mechanism of action of RFA is high‐frequency alternating current, generating high local temperatures that induce coagulative necrosis of the tissues 44 . This treatment approach has been proposed for pancreatic solid lesions, such as PC, NEN, SPN, and other malignant metastatic lesions; 7–21,45,46 however, only the feasibility and safety for treating for PC were assessed. Two ablation devices specifically designed for EUS are mainly used.…”
Section: Summary Of Reviewed Studiesmentioning
confidence: 99%
“…The other device was the Habib catheter (EMcision Ltd., London, UK). This is a monopolar electrode without a cooling system, which is inserted inside a standard EUS‐FNA needle and attached to an electrosurgical generator 19,20,45 . Different RFA needles/catheters and ablative energy settings were used in each study.…”
Section: Summary Of Reviewed Studiesmentioning
confidence: 99%
See 2 more Smart Citations